The Influence of Price and Quality of Products on The Purchase Decision of Bread Products - Devi Natalia; Nana Sutisna; Canggih Gumanky Farunik (Komunitas Dosen Indonesia, 2020)
The purpose of this study was to determine how big the influence between product quality and price on purchasing decisions at Roti. The study was conducted on 100 consumers of bread through the distribution of questionnaires. The method used in this research is descriptive method and qualitative method. In addition to calculating the relationship between the independent variable and the dependent variable, this study also calculated the relationship between variables. The correlation between product prices and purchasing decisions is 0.539, while the correlation between product quality and purchasing decisions is 0.296, so it can be said that the relationship between the three variables is quite strong and the product price variable has a positive relationship, while the product quality variable has a positive relationship. to purchasing decisions. From the results of the F test of model 1, the value of 81.846 was obtained and model 2 was found to be rated at 53.589, where the value is greater than the F table of 3.09, thus Ho is rejected and Ha is accepted. In the t-test, the results of t-count product quality are 5.924, and t-count prices are 3.776 when compared to t-table of 1